2010
DOI: 10.1111/j.1749-6632.2010.05735.x
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB and innate immunity in ischemic stroke

Abstract: Acute cerebral ischemia elicits an innate immune response that leads to a cascade of events that culminates in necrotic death of neurons and injury to their supportive structures in the neurovascular unit. Indeed, clinical studies have shown a close relationship between elevated levels of inflammatory markers and the risk for ischemic stroke. However, the signaling pathways that link these events are not well understood. A central regulator of inflammatory response is the transcription factor, nuclear factor-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
210
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 51 publications
3
210
0
1
Order By: Relevance
“…NF-κB is a master regulator of inflammation and immune responses [21]. It is potently activated in brain tissues from stroke patients and ischemic insulted animals [22]. The activation of NF-κB induces a Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB is a master regulator of inflammation and immune responses [21]. It is potently activated in brain tissues from stroke patients and ischemic insulted animals [22]. The activation of NF-κB induces a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-survival effect of NF-κB in neurons is mediated through the upregulation of several antiapoptotic proteins, including superoxide dismutase [25], Bcl-2, and Bcl-xL [26]. Studies have shown that the spatial and temporal control of NF-κB activation may determine whether it promotes neuronal death or survival [22]; however, the precise mechanisms underlying its effect in ischemic injury remains to be fully defined [24,[27][28][29]. Using neurons obtained from p65 +/− knockout mice, we showed the knockdown of NF-κB p65 moderately exacerbated OGD/R-induced neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The DAMPs act on TLR4 of microglia to activate the MyD88/NF-kB signaling pathway, which produces inflammatory factors that contribute to inflammatory injury and aggravate neurologic impairments (7). Thus, inhibition of TLR4 signaling strongly protects against cerebral ischemia (7,15).…”
Section: Discussionmentioning
confidence: 99%
“…Patten-associated molecular patterns and damage-associated molecular patterns (DAMPs) activate TLRs and induce the expression of NF-kB-dependent proinflammatory cytokines and/or type I IFN, and these molecules participate in pathophysiological processes (5). DAMPs released from ischemic neurons can activate the TLR4/MyD88/NF-kB signaling pathway in the neighboring microglia and induce the release of proinflammatory cytokines, which gives rise to the degeneration and apoptosis of neurons (6)(7)(8). Recent studies have shown that modification of the TLR-mediated NF-kB signaling pathway significantly attenuates ischemic injuries to the organs.…”
mentioning
confidence: 99%
“…Many attempts have been made to explore the mechanisms underlying this intrinsic neuroprotection of ischemic preconditioning. Postischemic inflammation is a significant factor that increases damage associated with ischemic brain injury [3,4] . Many studies have shown that the prevention of the inflammatory response might be a contributing mechanism by which IPC induces protection against brain ischemia [5,6] .…”
Section: Introductionmentioning
confidence: 99%